Respuesta :
answer is 1 1/12
3(1/4 + 1/2^2)+ (2x1/12)
3/4+1/4+2/12 (you get to this part by distributing 3 throughout the parentheses)
9/12+3/12+2/12= 1 1/12 hope this helps
3(1/4 + 1/2^2)+ (2x1/12)
3/4+1/4+2/12 (you get to this part by distributing 3 throughout the parentheses)
9/12+3/12+2/12= 1 1/12 hope this helps
Answer:
10/6
Step-by-step explanation:
First, we plug in for the variables in the equation.
3(1/4+(1/2^2)+2(1/12) =
3(1/4+1/4)+2/12 =
3(2/4)+2/12 =
3(1/2)+1/6 =
3/2+1/6.
Next, we need to have both of these fractions to have the same denominator, which is 6.
3/2*3/3+1/6 = 9/6+1/6 = 10/6
Hope this helps